1979
DOI: 10.1111/j.1365-2362.1979.tb01679.x
|View full text |Cite
|
Sign up to set email alerts
|

Polymyalgia arteritica: a clinical review

Abstract: In a series of thirty-seven consecutive patients with polymyalgia arteritica, twenty-five had polymyalgia rheumatica and twelve had cranial arteritis. Some failed to respond promptly to low doses of prednisolone and it is recommended that the initial dose should be in the order of 40 mg daily. An ESR above 40 mm in the first hour was present in four patients 3 months after admission; three were found to have rheumatoid disease and one pulmonary tuberculosis. Symptomatic relapses occurred in fourteen patients o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1980
1980
1993
1993

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…O'Duffy and associates reported that the correlation betweenabnormalbone scan results and the sites of muscle symptomswas so high that it suggested the myalgia might be due to the synovitis (5). Some investigators also have suggested the existence of a similarity in the pathogenesis of PMRand rheumatoid arthritis (6,7). In addition, it was demonstrated that early manifestations of rheumatoid arthritis may mimic PMR (8).…”
Section: Introductionmentioning
confidence: 99%
“…O'Duffy and associates reported that the correlation betweenabnormalbone scan results and the sites of muscle symptomswas so high that it suggested the myalgia might be due to the synovitis (5). Some investigators also have suggested the existence of a similarity in the pathogenesis of PMRand rheumatoid arthritis (6,7). In addition, it was demonstrated that early manifestations of rheumatoid arthritis may mimic PMR (8).…”
Section: Introductionmentioning
confidence: 99%